Impact of Change Management, Communication Effectiveness, and Organizational Readiness on Digital Transformation Success - Kasrim; Murcahyanto, Hary; Yusda, Desi Derina; Ghade, Fitalis (Malaqbi Publisher, 2025)
In today’s rapidly evolving digital era, organizations across all sectors face increasing pressure to transform their business processes, technologies, and cultures to remain competitive. This study investigates the impact of change management, communication effectiveness, and organizational readiness on digital transformation success. Using a quantitative research design, data were collected from 312 respondents representing various industries and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) in SmartPLS 4. The results reveal that all three constructs significantly and positively influence digital transformation success, with organizational readiness emerging as the strongest predictor. Furthermore, communication effectiveness partially mediates the relationship between change management and digital transformation success, while organizational readiness moderates this relationship. The model explains 68.4% of the variance in digital transformation success, demonstrating strong predictive and explanatory power. These findings confirm that successful digital transformation depends not only on technological investment but also on human-centric and organizational capabilities that ensure adaptability, clarity, and preparedness. The study contributes to theoretical advancement by integrating perspectives from change management, communication, and readiness theory within a unified framework. Practically, it offers guidance for leaders to enhance transformation outcomes by promoting transparent communication, structured change processes, and organizational readiness. Ultimately, this research underscores that digital transformation success is achieved when people, processes, and technology are strategically aligned under adaptive management.